The Form of Speech Video Game Vlogger’s MiawAug in Perspective the Strategy of Speaking by Levinson - Indah Rahmayanti; Ummul Qura; Rr. Sulistyawati; Egi Nusivera (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
Referring to the success of MiawAug, many novice creators have created YouTube channels with the same theme (video game reviews). One of the most important parts of creating YouTube content about video game reviews is the way of speaking strategies. With good speaking techniques, the communication style spoken by the creator will be more focused and conceptualized. Therefore, this study aims to describe the speech form of MiawAug as a Video Game Youtuber using Levinson's speech strategy perspective. The method used in this study is qualitative with a note-taking technique. The data source for this research is a YouTube video from the creator of MiawAug with video samples taken at random. The data analysis technique begins with making listening, making transcriptions, data reduction and analysis, and drawing conclusions. The results show that speakers prefer a no-nonsense strategy to build intimacy and positively use small talk strategies to increase their intimacy with the video viewers.Keywords: Speaking strategies, Video game’s vlogger, YouTuber MiawAug.